人肺癌A549细胞系肿瘤干细胞的筛选和鉴定 (Zhongguo Fei Ai Za Zhi, 2013)
BACKGROUND AND OBJECTIVE: Lung cancer stem cells are the root causes of lung cancer malignant phenotype and potential therapeutic target, the aim of this study is to isolate and characterize the cancer stem cells in the lung adenoearcinomas cell line A549, so as to provide an experimental basis for further stem cell research. METHODS: The cancer stem cells were isolated from the lung adenoearcinomas cell line A549 using FACS. And the difference of colony formation, cell proliferation and tumorigenicity in vitro were also tested. The expression of CD133 and ABCG2 were evaluated by RTPCR and Western blot. RESULTS: The percentage of SP cells was 5.93% of A549 and 0.32% of A549 afer incubation with verapamil. The results showed that there were signifcantly higher expression of CD133 and ABCG2 on SP cells than that of non-SP cells. And the ability of colony formation, cell proliferation and tumorigenicity in SP cell group were remarkably higher than that in non-SP cell group. CONCLUSION: Our results suggested that the cancer stem cells with higher expression of CD133 and ABCG2 can be isolated from the lung adenoearcinomas cell line A549 using FACS and be used in the further research experiments.